Magneto-structural variety of new 3d–4f–4(5)d heterotrimetallic complexes1. Issue 38 (14th October 2015) - Visinescu, Diana; Alexandru, Maria-Gabriela; Madalan, Augustin M.; Pichon, Céline; Duhayon, Carine; Sutter, Jean-Pascal; Andruh, Marius
<x xml:space="preserve">Abstract</x> Three families of heterotrimetallic chains with different topologies, have been obtained by reacting Schiff-base bicompartmental [CuII(L1)] complexes and lanthanide(iii) salts, with (NHBu3)3[M(CN)8] (M = MoV, WV).